Global policy responses to the COVID-19 pandemic: proportionate adaptation and policy experimentation: a study of country policy response variation to the COVID-19 pandemic - Arlina Dewi; Achmad Nurmandi; Erna Rochmawati; Eko Priyo Purnomo; Muhammad Dimas Rizqi; Abitassha Azzahra; Samantha Benedictos; Wahdania Suardi; Dyah Tri Kusuma Dewi (Tabriz University of Medical Sciences, 2020)
Background: Concern for the development of actions against COVID-19 has continued to grow since February 2020. Government responses remain a crucial part of preventing virus transmission through policy formulation and strengthening national capacity. Methods: This study has used quantitative analysis, using secondary data from 177 countries. The variables consist of Global Health Security (GHS) category and COVID-19 pandemic. An analysis of the appropriateness of the government's policy response in dealing with the COVID-19 pandemic was carried out by comparing the two variables. Results: The study indicated a significant relationship between global health security category and pandemic score (P < 0.01). There were 37 countries out of 177 (20.9%) categorized as under-reaction and least-reaction. Conclusion: Pandemic COVID-19 score, rated based on doubling time, is directly significant with the health security category. The government should improve its responsiveness and preparation to improve national capacity during the novel coronavirus pandemic.